2010
DOI: 10.1182/blood-2010-03-277079
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at LDLR locus may be associated with coronary artery disease through modulation of coagulation factor VIII activity and independently from lipid profile

Abstract: High levels of coagulation factor VIII (FVIII) have been associated with cardiovascular disease. Low-density lipoprotein receptor (LDLR) has been recently demonstrated to contribute to FVIII clearance from plasma. The aim of this study was to evaluate 3 single nucleotide polymorphisms in SMARCA4-LDLR gene locus (rs1122608, rs2228671, and rs688) and FVIII coagulant activity (FVIII:c) in subjects with (n ‫؍‬ 692) or without (n ‫؍‬ 291) angiographically confirmed coronary artery disease (CAD). High FVIII:c levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 49 publications
10
78
1
2
Order By: Relevance
“…More recent evidence shows that these plasma hemostatic proteins are also risk factors for other cardiovascular diseases (CVD) [4][5][6][7][8]. The broader role of FVIII and vWF is further supported by studies showing that genetic factors modulating the variability of these proteins are also associated with CVD.…”
Section: Introductionmentioning
confidence: 69%
“…More recent evidence shows that these plasma hemostatic proteins are also risk factors for other cardiovascular diseases (CVD) [4][5][6][7][8]. The broader role of FVIII and vWF is further supported by studies showing that genetic factors modulating the variability of these proteins are also associated with CVD.…”
Section: Introductionmentioning
confidence: 69%
“…We observed alteration in methylation patterns in genes previously associated with obesity and cardiovascular disease pathogenesis: stable methylation of MMP9 in PBLs, which has been associated with increased BMI in obese adults [45]; promoter hypermethylation of LDLR observed in patients with atherosclerosis [46] and for which genome-wide association studies have shown polymorphisms in individuals with coronary artery disease [47] and hypermethylation of GCK [48], FOXP1, MACROD2, JARID2, ZMIZ1 and the Genes were identified by bump hunting using a 1 kb window a Genes that also have DML maternally imprinted gene, KCNQ1 [49], as a predictor for type 2 diabetes susceptibility. The agreement between our results and those of previous studies suggests that altered methylation of metabolically relevant genes may be one mechanism by which IUGR leads to increased susceptibility to metabolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibition of both receptors by their highly specific ligand ␣-2-macroglobulin receptor-associated protein (RAP) (3,4) increased its half-life in mice (5,6). In humans, polymorphism in either LDLR or LRP is associated with elevated levels of FVIII (7)(8)(9)(10).…”
Section: Factor VIII (Fviii)mentioning
confidence: 99%